The Cost of Activity during the Rest Phase: Animal Models and Theoretical Perspectives - Nunez, Antonio A.; Yan, Lily; Smale, Laura (Frontiers in Endocrinology, 2018)
For humans, activity during the night is correlated with multiple pathologies that may reflect a lack of harmony among components of the circadian system; however it remains difficult to identify causal links between nocturnal activity and different pathologies based on data available from epidemiological studies. Animal models that use forced activity or timed sleep deprivation provide evidence of circadian disruptions that may be at the core of the health risks faced by human night and shift workers. One valuable insight from that work is the importance of changes in the distribution of food intake as a cause of metabolic imbalances associated with activity during the natural rest phase. Limitations of those models stem from the use of only nocturnal laboratory rodents and the fact that they do not replicate situations in which humans engage in work with high cognitive demands or engage voluntarily in nocturnal activity (i.e., human eveningness). Temporal niche switches by rodents have been observed in the wild, and interpreted as adaptive responses to energetic challenges; but possible negative outcomes, similar to those associated with human eveningness, have not been systematically studied. Species in which a proportion of animals shows a switch from a day-active to a night-active (e.g., grass rats) when given access to running wheels provide a unique opportunity to model human eveningness in a diurnal rodent. In particular, the mosaic of phases of brain oscillators in night-active grass rats may provide clues about the circadian challenges faced by humans who show voluntary nocturnal wakefulness.